Nilai pasar, aset tetap, profitabilitas, struktur modal, dan nilai perusahaan pada perusahaan yang melakukan IPO di tahun 2013 - Matilda, Matilda (Jurnal Manajemen Bisnis dan Kewirausahaan, 2017)
This research aims to find out the financial performance of firms that conducted an IPO of shares in the year 2013 which are listed in the Indonesian Capital Market (Bursa Efek Indonesia) for observation period 2013 until 2016, using Tobin’s Q model. To get the value of Tobin’s Q, data are collected from the internet, such as financial statements and closing stock prices. Companies with the highest Q value (overvalued condition) illustrate that the company has high investment growth. Which variations are influenced by variations of free variables such as market value, tangibility, profitability, and capital structure. The specific uniqueness is empirical data are generally applied to IPO-firms. Because IPO is a phenomenon of the early phase of growth. This research was conducted by using EViews 8. Model 1 uses a random effect model. Model 2 uses a fixed effect model. This research concludes that market value, tangibility dan profitability have a significant influence on capital structure. Furthermore, firm value would be more fit with capital structure as compared to profitability. Because the profitability of firms that conduct an IPO of shares is negative.